Structure-electronics relations of discotic liquid crystals from a molecular modelling perspective. Issue 13 (7th December 2016) - Said, Suhana Mohd; Mahmood, Mohamad Syafie; Daud, Mohammad Noh; Mohd Sabri, Mohd Faizul; Sairi, Nor Asrina
ABSTRACT: Discotic liquid crystals (DLCs) have been researched for their potential in electronics applications, such as organic field-effect transistors, organic light-emitting diodes and organic photovoltaics. These molecules generally comprise a rigid planar core surrounded by aliphatic chains, and self-organise into columnar phases. Charge transfer is enabled along these columns, as the spatial overlap of the stacked π orbitals within the columns lead to a quasi-one-dimensional conductivity. An understanding of charge transfer and electronics orbitals in the field of DLCs is valuable for rational design of future DLC molecules in electronics applications. This paper provides a perspective that a range of molecular modelling tools may bring into our understanding on the structure, dynamics and electronics properties of DLCs. Whilst the description of charge transfer of DLCs has been substantially investigated, the understanding on the molecular orbitals had been relatively less explored. We introduce a multiscale molecular mechanics and quantum mechanics approach to understanding the relationship between the bandgap and density of states (DOS) and the structural parameters of a DLC. This investigation is expected to be the starting point for situations where knowledge of DOS for DLCs are of the essence, in applications such as current rectification and thermoelectricity. GRAPHICAL ABSTRACT: